Kepuasan Kerja Karyawan di Rumah Sakit : Review Masalah dan Prospek di Era Digital - Nugroho, Sukmo Hadi; Gunawan, Kazan (Universitas Trunojoyo Madura, 2024)
Measuring employee job satisfaction in hospitals in the digital era shows that digital technologies, such as online survey platforms, mobile applications, and data analytics, have increased the efficiency of data collection and analysis. These technologies enable faster, more accurate, and more personalized job satisfaction assessments, helping management better understand employee conditions and respond to their needs effectively. However, major challenges arise related to employee data privacy, limited digital infrastructure in certain hospitals, and resistance from some employees who are less familiar with digital technology. These factors can affect the quality of the data obtained and employee trust in digital-based assessment systems. Recommendations for hospital management include developing flexible assessment systems, investing in digital training for employees, and ensuring data security and transparency in its use to build trust. These steps can help improve overall job satisfaction and retain quality healthcare workers amidst the challenges of the digital era.